Bilirubin Improves Gap Junction to Alleviate Doxorubicin-Induced Cardiotoxicity by Regulating AMPK-Axl-SOCS3-Cx43 Axis - Zhang, Siqi; Fan, Yixin; Zheng, Binbin; Wang, Yu; Miao, Chen; Su, Yue; Li, Kun; E., Yan; Wang, Xueli; He, Xueming; Wu, Xuefeng; Xu, Chenjie; et al. (Frontiers in Pharmacology, 2022)
Doxorubicin induces severe cardiotoxicity, accompanied by the high level of bilirubin in the blood. The conventional wisdom is that bilirubin is considered as a marker of liver damage. By contrast, here we aim to explore the potential protective effect of bilirubin on doxorubicin-induced cardiotoxicity, and investigate the mechanism for drug development. Doxorubicin was used to establish cardiotoxicity model in vitro and in vivo. The electrocardiogram (ECG), echocardiography and molecular biological methods were used to detect the effects of bilirubin on doxorubicin-induced cardiotoxicity. Consecutive intraperitoneal injection of bilirubin for 7 days significantly attenuated doxorubicin-induced arrhythmia, prolonged survival time and reduced the levels of aspartate aminotransferase (AST), lactate dehydrogenase (LDH), creatine kinase MB (CK-MB) and α-hydroxybutyrate dehydrogenase (α-HBDH) in mice. Bilirubin also markedly inhibited doxorubicin-induced phosphorylation of c-Jun N-terminal kinase (JNK) and connexin 43 (Cx43), and improved gap junction function in vitro and in vivo. In addition, bilirubin activated adenosine 5′-monophosphate (AMP)-activated protein kinase (AMPK) and induced suppressor of cytokine signaling 3 (SOCS3) expression, which was abolished by Axl inhibition. Moreover, pretreatment with AMPK agonist or AMPK inhibitor could mimic or abolish the cardioprotective effect of bilirubin on H9C2 cells in vitro, respectively. Altogether, bilirubin upregulates gap junctions’ function to protect against doxorubicin-induced cardiotoxicity by activating AMPK-Axl-SOCS3 signaling axis. We enrich the physiological function of bilirubin, and provide theoretical support for drug development.